A Bibliometric Analysis of Current Research on Life Insurance Lapsation - WEI, GAN JIA; Rossazana, Ab Rahim; Fatin Nur Hidayah, Taib Khan (HRMAS, 2025)
This paper aimsto provide a comprehensive analysis of the existing literature on life insurance lapsation. This paper applied a bibliometric analysis based on Scopus databases from 1895 to November 2024. Based on the “article title, abstract, keywords” search results, this paper finalised 221 documents for further analysis. BiblioMagika was employed to generate citation metrics, OpenRefine was utilised to clean and harmonise the dataset, and VOSviewer was used for data visualisation. This paper presented the results using bibliometric indicators, particularly document and source types, subject areas, publication trajectory, highly cited documents, most productive authors, publication distribution by countries and institutions, and author keyword analysis. As a result, most articles were published in journals, primarily in the economics, econometrics, and finance fields. The number of publications has increased since the early years, especially after the 2000s. Most of the literature was authored by Anna Rita Bacinello and Mogens Steffensen and focused on studies conducted in the United States. The author keyword of “life insurance” emerged as the most frequently used term in the field of life insurance lapsation. Thus, the analysis of existing literature provides valuable insights for scholars and policymakers, serving as a foundation for future research.